2020
DOI: 10.1007/s00339-020-03728-7
|View full text |Cite
|
Sign up to set email alerts
|

Conchixes: organic scaffolds which resemble the size and shapes of mollusks shells, their isolation and potential multifunctional applications

Abstract: Molluscan shells are an example of a mineral-based biocomposite material, and most studies to date have focused on understanding their biomineralization mechanisms. Meanwhile, large amounts of these shells are produced as waste globally by seafood which is used by other industries as a source of biogenic calcium carbonates. In this study, we propose a simple methodological approach for isolation of Conchixes, the organic scaffolds that resemble the size and shapes of mollusks shells, using gentle EDTA-based de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 115 publications
2
17
0
Order By: Relevance
“…Our review of numerous recent scientific publications on biomineralization has revealed emphasis of the overall scientific attention towards calcification [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], biosilicification [ 14 , 15 , 16 ], biomagnetism [ 17 , 18 ], and multiphase biomineralization [ 19 , 20 , 21 , 22 , 23 ]. Traditional objects of study continue to include molluscs [ 24 , 25 , 26 , 27 , 28 ], sea urchins [ 29 ], and skeletal structures such as eggshells [ 30 ], teeth [ 31 , 32 ], and bones [ 33 , 34 , 35 , 36 ]. While it is understandable to focus on the biomineralizing organisms typically encountered by humans on Earth, this focus tends to overlook a variety of distinct biomineralization pathways seen in extremophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of numerous recent scientific publications on biomineralization has revealed emphasis of the overall scientific attention towards calcification [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], biosilicification [ 14 , 15 , 16 ], biomagnetism [ 17 , 18 ], and multiphase biomineralization [ 19 , 20 , 21 , 22 , 23 ]. Traditional objects of study continue to include molluscs [ 24 , 25 , 26 , 27 , 28 ], sea urchins [ 29 ], and skeletal structures such as eggshells [ 30 ], teeth [ 31 , 32 ], and bones [ 33 , 34 , 35 , 36 ]. While it is understandable to focus on the biomineralizing organisms typically encountered by humans on Earth, this focus tends to overlook a variety of distinct biomineralization pathways seen in extremophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, conchixes completely repeat the size and shapes of the shells. In the future, molluscan shells may have broad applications in biomineralization [ 230 ].…”
Section: Biomaterials From Marine Organismsmentioning
confidence: 99%
“…This effect was attributed to calcium, which, after being administered to the wound tends to enhance the healing process [329,330], though the authors do not rule out the possibility of so-called conchix proteins to be involved in the facilitation of the healing process. Conchix, a term representing the shell organic matrix, has been recently proposed by Ehrlich and co-workers [331] to underline the importance of this organic piece of mollusc shell architecture. A brief summary on conchiolin properties is provided by Table 11.…”
Section: Conchiolin and Conchixes Of Molluscan Originmentioning
confidence: 99%